Democracy in theory and practice - Elstub, Stephen ([S.l.] : Routledge, 2012)
Democracy is an issue of major importance in theory and practice in politics throughout the world. However, democracy$1 (Bs study and advancement has been significantly compromised by a dichotomy between theorising about democracy, and empirical studies of democracy in practice. In addition to highlighting the need for this gap to be overcome, this book contributes to overcoming this divide, by demonstrating a number of ways that democracy in theory and practice can be synthesised; deepening our understanding of the relationship between democracy in theory and practice in the process. Different, but related, democratic principles and concepts are considered such as legitimacy, political equality, deliberation, and participation. A range of practical contexts are also investigated including multi-level polities, deeply divided societies, whole polities, local rural and urban areas, and a range of democratic processes, innovations and spectacular events. Moreover, the book sets the agenda for future work to combine democracy in theory and practice. This book was originally published as a special issue of Representation.s
Keywords: Democracy; Democracy--Philosophy